POSITIVE PSCHOLOGY AND PSYCHOLOGICAL RESILIENCE - Güldener ALBAYRAK (International Journal of Eurasia Social Sciences, 2018)
The purpose of this study is to examine the concept of psychological resilience, which is under the scope of positive psychology. This study is a descriptive one. The findings were obtained through examination of related literature. Positive psychology is an area of psychology focusing on people’s positive characteristics like well-being, satisfaction from life, being psychologically resilient and happiness. Psychological resilience, one of these positive characteristics, are cognitive and behavioral efforts shown by individuals to control internal or external demands exceeding or challenging the irresources. Psychological resilience can be defined as an individual’s skill and capacity to cope with experiences that can lead to negative results in their life using their personal, family and social resources, to adapt after these experiences and to continue functioning. This capacity and skill can change and improve over time. The personal, family and social factors that the individuals have can get stronger or increase. There are many factors contributing to psychological resilience: biological factors like health, genetic predisposition, temperament and sex, personality traits like cognitive competence and ability to cope, psychological factors like positive self-esteem, self-efficacy, self-awareness, internal locus of control, optimism, motivation, curiosity and positive depiction of interpersonal relationships, family environment and environment outside the family. It is believed that individuals’ psychological resilience levels can be increased through improving these factors.